2016
DOI: 10.1111/1460-6984.12261
|View full text |Cite
|
Sign up to set email alerts
|

Promoting linguistic complexity, greater message length and ease of engagement in email writing in people with aphasia: initial evidence from a study utilizing assistive writing software

Abstract: This study provided some initial evidence that assistive writing technologies can support people with aphasia in email writing across a range of important performance parameters. However, more research is needed to measure the effects of these technologies on the writing of people with aphasia, and to determine the optimal compensatory mechanisms for specific people given the linguistic-strategic resources they bring to the task of email writing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 39 publications
(62 reference statements)
3
31
0
Order By: Relevance
“…Thiel et al . () similarly found that their technology‐enhanced therapy only improved writing performance when the technology was available. Therefore, they also concluded that the writing impairments of their participants were untouched, and that treatment effects were compensatory.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations
“…Thiel et al . () similarly found that their technology‐enhanced therapy only improved writing performance when the technology was available. Therefore, they also concluded that the writing impairments of their participants were untouched, and that treatment effects were compensatory.…”
Section: Introductionmentioning
confidence: 91%
“…The first was WriteOnline TM . This incorporates word prediction, vocabulary support in the form of individualized wordbars, and text-to-speech conversion, all of which have been shown to assist people with dysgraphia (e.g., Thiel et al 2017). It also provides mind maps, which help to organize written work.…”
Section: Assistive Technologymentioning
confidence: 99%
See 2 more Smart Citations
“…Non-pharmacological approaches have been shown to aid rehabilitation in dysgraphia. Non-pharmacological treatments used include spelling therapy, PA, RTMS, relearning in based spelling therapies on functional writing with unity-modal and multi-modal therapies, technology-enhanced writing therapy using assistive writing software to improve email writing, and rereading treatment with slow reading coupled interactive spelling treatment with errorful spelling (8,12,13,15,(24)(25)(26)(27). The novelty of the present study was without writing practice, a new suggestion was provided for dysgraphia pattern and rehabilitation of dysgraphia, neglect and disability function.…”
Section: Discussionmentioning
confidence: 99%